Explorative Study on the Role of Artificial Intelligence in Indian Eldercare: Insights from Elderly Individuals and Healthcare Providers - Chattopadhyay, Amarnath (Digital Repository of Theses, 2026)
This research proposal provides an explorative study reviewing the impact of artificial intelligence (AI) in Senior Care in India, acquiring the view point elderly individuals , healthcare providers. & AI Solution providers. With a fast greying population which is estimated to reach 350 million by 2050, India is up for a major difficulties to provide decent healthcare to the seniors live in rural areas in a suboptimal Financial conditions and their families being away in cities which necessitates finding an unique solution which is effective. Some of the contributing factors which impact the research are captured in the study . The malaise of lifestyle diseases like Diabetes and High Blood Pressure , the migration of the population towards cities in search of livelihood and leaving the seniors behind in the rural areas making them vulnerable on health care and finally the usage of AI based health care initiatives like Remote monitoring , medication schedule adherence and a few like that are recorded The expected outcome of this study is to provide awareness on the ground realities which would finally enhance the quality of living standard for Indian elders. There had been some work done previously in AI based solutions on senior care in India, but no substantial research has happened on the interplay among the elders, care givers and AI solution providers. Taking a composite approach this study finally wants to bring out insights which will assist the Industry and decision makers to formulate approach and policies to boost senior care in India. The expected outcome of this study is to provide awareness on the ground realities which would finally enhance the quality of living standard for Indian elders